Productivity of [18F] PSMA in relation to initial [18F] activities: A Preliminary Cyclotron-Based Study - Biswasarma, Sanchoy Chandra; Azim, Mohammad Anwar Ul; Islam, Md Ariful; Islam, Sanjida; Khatun, Mst Afifa; Mehdi, Hasan; Mia, Md Shohag; Siddiqee, Nur E Alam; Kadir, Muhtasim; Mamun, Mustafa; Podder, Priyanka; Hossain, Nahid (Bangladesh Journal of Nuclear Medicine, 2026)
Prostate cancer is becoming clinical concern in Bangladesh, raising the need for advanced imaging for accurate diagnosis and patient management. [18F] PSMA-1007 is an attractive PET radiopharmaceutical because the longer half-life of 18F (Fluorine-18) supports centralized cyclotron-based production and distribution to nearby PET centres. A preliminary comparison was performed using two production runs carried out under high- and moderate-activity conditions at EOB. In the first run, the EOB activity was 4648 mCi. Despite the higher starting activity, the final product activity was only 95 mCi, with a decay-corrected activity of 126.99 mCi and a decay-corrected radiochemical yield (RCY) of 2.7%. In the second run, the EOB activity was lower at 2300 mCi, yet the final product activity increased to 1200 mCi, with a decay-corrected activity of 1604 mCi and a decay-corrected RCY of 69.75%. These findings indicate that higher starting activity does not necessarily result in successful [18F] PSMA-1007 production. Rather, excessive starting activity may adversely affect the radiolabelling process. In contrast, a moderate starting activity may provide more favourable conditions for efficient labelling and product recovery. This preliminary study highlights the importance of optimizing EOB activity to achieve reliable cyclotron-based production of [18F] PSMA-1007 for routine prostate cancer imaging services in Bangladesh. Bangladesh J. Nuclear Med. 29(1): 73-78, 2026